Принципи законотворчої діяльності - Климчук, Т.; Klimchuk, T. (Східноєвроп. нац. ун-т ім. Лесі Українки, 2013)
У статті досліджено актуальні питання, пов’язані із визначенням змісту та системи принципів законотворчості. Зроблено спробу виявити критерії систематизації принципів законотворчості та запропоновано поділ принципів законотворчості на загальні й процедурні (спеціальні). In this article we analyze general theoretical questions of specification the fundamental principles of lawmaking. The latter is a type of juridical activity, which generates legal result that has a certain influence on social relations, that is, - a law. This is why specification of principles of lawmaking, of their meaning, and of their system is one of the main directions in studying of lawmaking process. We made an attempt to reveal the criteria of systematization of lawmaking principles and we suggest dividing principles of lawmaking into general and procedure (special). Among first we propose to consider the supremacy of law, inadmissibility of narrowing the rights and freedoms of man and citizen in content and volume, publicity, humanism, democratism, legality, scientific nature, consistency, etc. To procedure (special) principles we ascribe efficiency, planning, professionalism, excellence in juridical technique, considering former lawmaking experience. We also focus on necessity to employ anthropocentric ideas in creating the system of lawmaking principles.
The Principles of Lawmaking
Keywords: законотворчість; принципи законотворчості; загальні принципи законотворчості; lawmaking; principles of lawmaking; general principles of lawmaking